(untitled) (Comparative Professional Pedagogy, 2023)
The article is devoted to the retrospective analysis of the development of pharmaceutical education in Great Britain. It is established that pharmaceutical education in Great Britain has a rich history that dates back to the middle of the 19th century. The modern history of pharmacy in Great Britain can be traced back to the founding of the Pharmaceutical Society in 1841. It is stated that the Royal Pharmaceutical Society of Great Britain has become the main professional organization of pharmacists. It is found that the first colleges of pharmacy in Great Britain were founded in the mid-19th century, with the first Bachelor of Pharmacy (BSc) degree offered by the University of Manchester (1904). In 1921, the University of London first began training pharmacists on a three-year Bachelor’s Program of Pharmacy (BPharm). It is established that in the second half of the 29th century in Great Britain, faculties of pharmacy were founded in universities and Bachelor’s and Master’s education programs in the field of pharmacy were introduced. The three-year BPharm program was discontinued in 1997 along with other undergraduate programs. It was replaced by the four-year Master of Pharmacy (MPharm) program in order to meet the requirements of the European Pharmacists Directive and Training Directive of 1985. The bodies and organizations of the pharmaceutical industry of Great Britain, which provide its management and regulation, are characterized. The main regulatory and legal documents regulating the activities of universities in Great Britain and legislation in the field of pharmaceuticals and pharmaceutical education are analyzed. It is defined that recently pharmaceutical education in the UK has been fundamentally changed since 2012 with the introduction of "integrated" educational programs for the training of pharmacists and is acquiring new dimensions, in particular in the direction of the development of clinical pharmacy and patient-oriented practice. It is concluded that pharmaceutical education in Great Britain is well organized and provides future pharmacists with a wide range of knowledge and skills.